Relationship Between Basic Psychological Needs and Mental Vitality in the Elderly - Mehdi Arabzadeh (University of Social Welfare & Rehabilitation Sciences, 2017)
Objectives Subjective vitality refers to a positive feeling of aliveness and energy.  This condition is important in the aging period; therefore, the purpose of this study was to investigate the relationship between basic psychological needs with subjective vitality in the elderly. Methods & Materials It is a functional and cross-sectional study. The research sample included 235 elderly  who were selected by convenience sampling method. The participants completed the subjective vitality and basic psychological needs scales. To conduct the necessary descriptive and inferential statistical operations, SPSS (Version 23) was used. Mean and standard deviation were utilized to analyze the data in the descriptive statistics section, and in inferential statistics section, step-by-step multiple regressions were used to predict subjective vitality. Results The results showed that subjective vitality has a positive and meaningful relationship with autonomy (P<0.01, r=0.60), competence (P<0.01, r=0.53), and relatedness (P<0.01, r=0.58) in the elderly population. Also, the basic psychological needs can be explained by 31% of variance subjective vitality in elderly people. Conclusion The basic psychological needs are considered as an important factor for maintaining subjective vitality in the elderly. Therefore, understanding the basic psychological needs and strengthening these factors can be an effective method for enhancing the subjective vitality of elderly people.